The social and economical accompayings of money laundering crime under globalization: A study of contemporary crime accordig to social and econominal dimensions associated to globalization - Ali, Hussain Ismail (Al-Adab Journal, 2020)
The crime of money launderying was exponded in the begnining of nineteenths as a result of the changes of social and economical globalization shifting due to its excess to the national limits in trade, finance and information networks . The speed developments in globalization field created new progress and technology to commit crimes specially in money launderying and it become the focused point of the thinkers ,socialists , economicsts and legal people over the world to study this phenomend which progresses too quickly . This study consists of two chapter . The first one is the general frame of it and it includes three sections , the first one is the general frame , the second is about the concepts and the last one related to the previous studies. The second chapter deals with the sociological , economical and religious explession for money launderying crime and it consists of four section . The sociology changes of money loundying is in the first one . The extand of money launderying crime if found in the second one while the third one treats Islam expression for this phenomend and the last one deals with the economical and social changes and accompayings of money launderying . Finally the researcher has shown the conclusions , recommendations and suggestions then the list of the sources one presented.